KORELASI KETERAMPILAN MEMAHAMI TEKS ANEKDOT DENGAN KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS X SMA NEGERI 3 PADANG PANJANG - Marisa, Winda; Arief, Ermawati; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTThis article was written to describe the relation of reading undestanding skill of anecdote texts to the skill of writing the text of the anecdote of students of class X SMA Negeri 3 Padang Panjang. This research is a quantitative research with descriptive method and correlational design. The sample in this study amounted to 40 people. The data of this research is score of skill test result reading understanding the anecdote text and skill test result writing the text of anecdote. The data were gotten through an objective test intended to measure the student’s reading understanding of anecdote text and a performance test intended to measure the students skills of writing the text of anecdote. Based on data analysis and discussion, the following three things are obtained. First, the skill of writing the text of anecdote of the students class X of SMA Negeri 3 Padang Panjang is in good qualification (82,29). Second, the skill of reading understanding to the anecdote text of the students of class X SMA Negeri 3 Padang Panjang is in very good qualification (87,50). Third, there was a significant corelation between the students reading understanding of anecdote text with the skills of writing the anecdote text of strudent of class X SMA Negeri 3 Padang Panjang in which the significance level 95% with the degrees of freedom n-1 (dk = n-1). Based on research result and data analysis, we get the conclusions, that is there are significant relations of reading understanding skills and writing skills about anecdote text of ten grade SMA Negeri 3 Padang Panjang because we get that tcount > ttable i.e 2,228>1,68.Kata kunci: korelasi, keterampilan memahami, keterampilan menulis, teks anekdot